2008
DOI: 10.1016/j.juro.2008.03.064
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Lymphatic Sparing Varicocelectomy in Adolescents

Abstract: Laparoscopic lymphatic sparing varicocelectomy is preferable to an open or laparoscopic Palomo repair that does not preserve the lymphatics. It has a significantly lower incidence of postoperative hydroceles, especially those requiring surgical intervention, and still maintains a low incidence of persistence/recurrence. The procedure is especially advantageous for bilateral varicocelectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 15 publications
0
37
1
3
Order By: Relevance
“…[4][5][6] Initially open surgical approach was the standard, but now there are alternative approaches, such as embolization and laparoscopy. 7,8 The effect of varicocelectomy on semen analysis is controversial. Many articles report favourable outcomes, 9-11 and others do not.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Initially open surgical approach was the standard, but now there are alternative approaches, such as embolization and laparoscopy. 7,8 The effect of varicocelectomy on semen analysis is controversial. Many articles report favourable outcomes, 9-11 and others do not.…”
Section: Introductionmentioning
confidence: 99%
“…Preservation of lymphatics is strongly advised in varicocelectomy for the superior postoperative outcome. Magnification that allows identification and preservation of the lymphatics can reduce the rate of hydrocele [9,27]. In our study, 23.6 % (29/123) lymphatics were to be ligated for incorrect identification in the ''nonmicroscopic varicocelectomy,'' but in the microsurgical varicocelectomy, an average number of 2.93 (123/42) lymphatics was identified and preserved.…”
Section: Discussionmentioning
confidence: 57%
“…1 Recently, studies have shown that varicocele is a bilateral disease, 2 with direct effect on the development of benign prostatic hyperplasia (BPH) and prostate cancer. 3,4 Other recent studies have shown that the prevalence of malfunction of one-way valves in the ISV increases by 10-15% for each decade of life.…”
Section: Editorial Comment To Umbilical Laparoendoscopic Single Site mentioning
confidence: 99%
“…Laparoscopic surgery is especially advantageous for bilateral varicocelectomy. 1,2 However, a comparative study showed no superiority of laparoscopic varicocele ligation over the standard open subinguinal varicocelectomy with respect to operative time, postoperative pain, cost-effectiveness and complications. [5][6][7] Laparoendoscopic single site surgery (LESS) was introduced several years ago.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation